Dynamics of conflicts in waste management: A review of literature and global issue mapping (2020-2025) - Qurnia Indah Permata Sari (Education and Development Research, 2025)
Policy conflicts in waste management are increasingly recognized as central challenges in environmental governance, particularly within decentralized and urbanizing contexts. This study conducts a bibliometric analysis of 42 peer-reviewed journal articles published between 2020 and 2025 to map global research trends and identify thematic gaps in the study of waste governance conflicts. Using the Policy Conflict Framework (PCF) as an analytical lens, we examine the interplay of actors, interests, and institutional dynamics shaping policy disputes across different countries and governance settings. The results reveal a modest but significant body of literature, with annual publication rates peaking in 2023 before declining in 2025. Despite this decline, citation analysis suggests that interest in the topic remains active. Keyword and co-occurrence analyses show a dominance of terms such as “governance” and “urban waste,” while conflict-related concepts remain marginal, indicating a persistent gap in integrating political perspectives into waste management research. Thematic maps further demonstrate that while technical and sustainability themes are well-established, conflict resolution, intergovernmental frictions, and participatory governance remain underdeveloped. This review underscores the importance of expanding conflict-sensitive approaches to environmental policy. By combining bibliometric insights with PCF, we propose a more nuanced understanding of how stakeholder resistance, institutional fragmentation, and regulatory misalignment influence waste governance outcomes. The study concludes with recommendations for future research and policy, emphasizing the need for multi-actor, theory-informed, and context-sensitive frameworks to address the complex realities of conflict in waste management systems.